Menyelidiki Faktor Penyebab dari Quiet Quitting Melalui Tinjauan Sistematis - Dicky Dienial Habibillah Wijaya; Nida Hasanati; Rizki Maulana Hidayatullah (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2026)
This study examines the factors influencing the phenomenon of quiet quitting in the context of contemporary organizations by reviewing empirical evidence published between 2021–2024. Quiet quitting refers to the psychological withdrawal of employees who remain formally employed but consciously limit their work involvement to the minimum required by the contract without any explicit intention to quit. Although this phenomenon has been widely discussed in academic literature, much of the research still examines quiet quitting in a fragmented way, lacking a comprehensive theoretical framework. This study adopts a systematic review approach following PRISMA 2020 guidelines, analyzing eight empirical articles indexed in Scopus and Google Scholar. The findings indicate that quiet quitting is influenced by individual factors such as burnout, emotional exhaustion, reduced job satisfaction, and low work engagement. Organizational factors include psychological contract violations, low perceived organizational support, unsupportive leadership styles, excessive workload, and an exclusive work culture. The findings can be understood within the Job Demands–Resources framework, where the imbalance between work demands and organizational resources triggers disengagement. This study contributes theoretically by integrating empirical findings into a more cohesive conceptual framework and provides practical implications for human resource management aimed at improving engagement and organizational sustainability.